Unsedated In-office Transgastrostomy Esophagoscopy to Monitor Therapy in Pediatric Esophageal Disease. Issue 1 (January 2018) - Hall, Caroline H.T.; Nguyen, Nathalie; Furuta, Glenn T.; Prager, Jeremy; Deboer, Emily; Deterding, Robin; Menard-Katcher, Calies; Capocelli, Kelley E.; Kramer, Robert E.; Friedlander, Joel A.
Abstract : ABSTRACT: Monitoring therapy in esophageal inflammatory disorders such as eosinophilic esophagitis and reflux esophagitis often requires frequent endoscopic evaluation. We recently reported the effective use of unsedated in-office transnasal esophagoscopy that significantly decreased costs and anesthetic exposure associated with pediatric esophagoscopy in eosinophilic esophagitis. Here we report a series of pediatric patients with esophagitis with gastrostomy tubes who underwent unsedated transgastrostomy esophagoscopy (TGE) in an office setting. Nine patients (ages 16 months–21 years) tolerated TGE without significant adverse events. Biopsy specimens were adequate for evaluation. This series confirms that unsedated in-office TGE can be used to successfully obtain mucosal biopsies to monitor esophageal inflammatory conditions in children without the use of sedation.